Add-on Pyridostigmine Enhances CD4+ T-Cell Recovery in HIV-1-Infected Immunological Non-Responders: A Proof-of-Concept Study - Valdés-Ferrer, Sergio I.; Crispín, José C.; Belaunzarán-Zamudio, Pablo F.; Rodríguez-Osorio, Carlos A.; Cacho-Díaz, Bernardo; Alcocer-Varela, Jorge; Cantú-Brito, Carlos; Sierra-Madero, Juan (Frontiers in Immunology, 2017)
Background In human immunodeficiency virus (HIV)-infection, persistent T-cell activation leads to rapid turnover and increased cell death, leading to immune exhaustion and increased susceptibility to opportunistic infections. Stimulation of the vagus nerve increases acetylcholine (ACh) release and modulates inflammation in chronic inflammatory conditions, a neural mechanism known as the cholinergic anti-inflammatory pathway (CAP). Pyridostigmine (PDG), an ACh-esterase inhibitor, increases the half-life of endogenous ACh, therefore mimicking the CAP. We have previously observed that PDG reduces ex vivo activation and proliferation of T-cells obtained from people living with HIV. Methods We conducted a 16-week proof-of-concept open trial using PDG as add-on therapy in seven HIV-infected patients with discordant immune response receiving combined antiretroviral therapy, to determine whether PDG would promote an increase in total CD4+ T-cells. The trial was approved by the Institutional Research and Ethics Board and registered in ClinicalTrials.gov (NCT00518154). Results Seven patients were enrolled after signing informed consent forms. We observed that addition of PDG induced a significant increase in total CD4+ T-cells (baseline = 153.1 ± 43.1 vs. week-12 = 211.9 ± 61.1 cells/µL; p = 0.02). Post hoc analysis showed that in response to PDG, four patients (57%) significantly increased CD4+ T-cell counts (responders = 257.8 ± 26.6 vs. non-responders = 150.6 ± 18.0 cells/µL; p = 0.002), and the effect persisted for at least 1 year after discontinuation of PDG. Conclusion Our data indicate that in patients with HIV, add-on PDG results in a significant and persistent increase in circulating CD4+ T-cells.